The role of independent directors in strengthening corporate governance - Musman, Musliha; Mohamed Sadique, Raziah Bi; Muda, Salwa (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Corporate governance refers to the system by which organisations are directed and controlled to protect shareholder and stakeholder interests through accountability, transparency, and responsible decision-making. Rooted in agency theory, it addresses conflicts arising from the separation of ownership and control by establishing monitoring mechanisms to align managerial actions with shareholder interests. Contemporary perspectives extend beyond reducing agency costs to emphasise long-term value creation, ethical conduct, sustainability, and stakeholder trust, including the integration of environmental, social, and governance (ESG) considerations into corporate practices.